2003
DOI: 10.1038/sj.jhh.1001590
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate associates of QT interval parameters in diabetic patients with arterial hypertension: importance of left ventricular mass and geometric patterns

Abstract: The aim of the study was to assess the determinants of increased QT interval parameters in diabetic patients with arterial hypertension and, in particular, the strength of their relationships to echocardiographically derived left ventricular mass (LVM) and geometric patterns. In a cross-sectional study with 289 hypertensive type 2 diabetic outpatients, maximal QT and QT c (heart ratecorrected) intervals, and QT, QT c , and number-of-leadsadjusted QT interval dispersions were manually measured from standard bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
(56 reference statements)
3
21
0
Order By: Relevance
“…5,16,17 In brief, all adult type 2 diabetic outpatients that had standard ECGs recorded from July 1994 to June 1996 were enrolled in this prospective study. This protocol complied with the ethical guidelines of the Declaration of Helsinki, was approved by the local ethics committee and all participants gave written informed consent.…”
Section: Subjects and Baseline Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…5,16,17 In brief, all adult type 2 diabetic outpatients that had standard ECGs recorded from July 1994 to June 1996 were enrolled in this prospective study. This protocol complied with the ethical guidelines of the Declaration of Helsinki, was approved by the local ethics committee and all participants gave written informed consent.…”
Section: Subjects and Baseline Proceduresmentioning
confidence: 99%
“…17 Two-dimensionally guided M-mode images were obtained from the short axis parasternal view at the level of the tips of the mitral valve leaflets and the measurements of interventricular septal wall thickness (ISWT), posterior wall thickness (PWT) and left ventricular end diastolic diameter (LVEDD) were made at the peak of the ECG R wave according to the Penn convention. 19 Left ventricular mass (LVM) was calculated by the anatomically validated formula of Devereux and Reichek:…”
Section: Subjects and Baseline Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Prolonged QT interval duration or dispersion are associated with the occurrence of life-threatening ventricular arrhythmias and thus are presumed to represent potential predictors of increased cardiovascular risk. 5 In patients with hypertension, QT interval parameters have mainly been associated with left ventricular mass, 6,7 although 2 studies 8,9 suggested that they are no better than simple electrocardiographic voltage criteria for LVH detection. Moreover, it has been reported recently that they probably constitute true cardiovascular mortality markers in hypertensive patients.…”
mentioning
confidence: 99%
“…Prolonged recovery from electrical excitation increases the likelihood of dispersing refractoriness, when some parts of myocardium might be refractory to subsequent depolarization. 33 In animal experiments, prolongation of the QT interval is a direct myocardial pesticide effect and is independent of cholinergic effects. 34 Other common cardiac manifestations include sinus tachycardia.…”
Section: Discussionmentioning
confidence: 99%